“Bertengkar” (Quarrel): The Diagnosis of Componential Meaning In Jambi Malay Language - dian mukhlisa (English Literature Department, Adab and Humanities Faculty, 2019)
This paper studies the componential meaning of word “bertengkar” indicating the meaning “quarrel” in Jambi Malay Language. It aims to identify meaning relation of each word relate to quarrel in Jambi Malay. It is a descriptive qualitative research using interview technique in collecting the data. The result shows that there are 5 (five) type of verbs indicating the meaning “to quarrel” in Jambi Malay Language, namely 1. Betinju (to quarrel by hand, man-man) ; 2. Belago (to quarrel by hand and foot, man-man, animal-animal); 3. Begoco (to quarrel by hand and foot, young man- young man ); 4. Becekak (to quarrel by speech/ mouth, man - man) ; 5. Bekelai (to quarrel by hand and foot, man-man).